Association between exposure to family planning messages on different mass media channels and the utilization of modern contraceptives among young women in Sierra Leone: insights from the 2019 Sierra Leone Demographic Health Survey. - Sserwanja, Quraish; Turimumahoro, Patricia; Nuwabaine, Lilian; Kamara, Kassim; Musaba, Milton W. (BMC Women's Health, 2022)
Background: Access to sexual and reproductive health information enables young women to make appropriate decisions. We examined the association between exposure to family panning messages on different mass media and the use of modern contraceptives among young women in Sierra Leone.Methods: This was a secondary analysis of the 2019 Sierra Leone Demographic and Health Survey data of young women aged 15-24 years. Multistage stratified sampling was used to select study participants in the survey. We used multivariable logistic regression to determine the association between exposure to family panning messages on different types mass media channels and utilization of modern contraceptives. All our analyses were done using SPSS version 25.Results: Out of 6055 young women, 1506 (24.9%, 95% CI 24.0-26.2) were utilizing a modern contraceptive method with the prevalence higher among urban women (26.5%) compared to rural women (23.1%). Less than half (45.6%) had been exposed to family planning messages on mass media (radio 28.6%, television 10.6%, mobile phones 4.2% and newspapers or magazines 2.2%). Young women who had exposure to family planning messages on radio (AOR: 1.26, 95% CI 1.06-1.50) and mobile phones (AOR: 1.84, 95% CI 1.25-2.69) had higher odds of using modern contraceptives compared to their counterparts without the same exposure. Furthermore, having access to internet (AOR: 1.45, 95% CI 1.19-1.78), working (AOR: 1.49, 95% CI 1.27-1.74), being older (20-24 years) (AOR: 1.75, 95% CI 1.46-2.10), being married (AOR: 0.33, 95% CI 0.26-0.42), having visited a health facility within the last 12 months (AOR: 1.34, 95% CI 1.10-1.63), having secondary (AOR: 2.83, 95% CI 2.20-3.64) and tertiary levels of education (AOR: 3.35, 95% CI 1.83-6.13), higher parity (having above one child) AOR: 1.57, 95% CI 1.19-2.08) and residing in the southern (AOR: 2.11, 95% CI 1.61-2.79), northwestern (AOR: 1.87, 95% CI 1.39-2.52), northern (AOR: 2.11, 95% CI 1.59-2.82) and eastern (AOR: 1.68, 95% CI 1.27-2.22) regions of residence were associated with higher odds of modern contraceptives utilization.Conclusion: In Sierra Leon, only one in four young women were using modern contraception and more than half of them had not had any exposure to family planning messages on the different types of mass media channels. Behavior change communicators can prioritize family planning messages using radio, mobile phones and the internet. In order to publicize and encourage young women to adopt healthy behaviours and increase uptake of modern contraceptive.